Habit Literacy sebagai Strategi Penguatan Karakter dan Produktivitas Remaja di Era Distraksi Digital - Ihya Ulumudin; Masduki Asbari; Khusnul Aulia; Dwiki Ramadani (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
Habits are the foundational behaviors that shape the personality and efficiency of individuals, particularly among the youth undergoing the identity development process. The objective of this article is to examine the impact of constructive and destructive habits on the traits and efficiency of the younger generation, with reference to Sabrina Ara's work titled Is It Bad or Good Habits (2022). In an era marked by pervasive social media use, digital habits such as endless scrolling, binge-watching, and multitasking have become significant issues influencing the thought processes and morals of young individuals. Utilizing a qualitative approach and literature review methodology, this article synthesizes Ara's insights with theories from behavioral psychology, character education, and the philosophy of action. The research findings indicate that habits cannot be classified as entirely positive or negative; rather, their implications depend on the context, purpose, and effects on personal development. Therefore, character education must integrate habit literacy as an effort to mold a strong and productive generation.